Navigasi UAV Otonom Multi-Landing Berbasis Finite State Machine Menggunakan Algoritma Waypoint Follower pada ROS2 - Pipit Anggraeni; Hilda Khoirunnisa; Alif Prima Utama (Fakultas Ilmu Komputer, 2026)
Challenges in medical logistics, such as geographical limitations, urban congestion, and ground transport risks, necessitate efficient and safe delivery solutions. Unmanned Aerial Vehicles (UAVs) offer a promising alternative. This research aims to develop and implement an autonomous UAV navigation system capable of complex multi-landing missions, validated for medical delivery scenarios. The system employs a hierarchical control architecture, integrating the Robot Operating System 2 (ROS2) as the high-level mission supervisor with the PX4 flight controller for low-level control. Mission logic, including navigation using the Waypoint Follower algorithm and landing sequences, is formally governed by a Finite State Machine (FSM) implemented in ROS2. Communication between ROS2 and PX4 is facilitated by Micro XRCE-DDS. System validation was performed via Software-in-the-Loop (SITL) simulation using Gazebo, featuring a mission scenario with four waypoints and one intermediate landing. Simulation results demonstrated that the system successfully completed the entire mission autonomously (100% success rate). Quantitative analysis of position accuracy revealed total position errors () between 1.35 m and 1.57 m during navigation phases, and an error of 0.84 m at the intermediate landing. Errors were found to be consistently dominant on the Y-axis. In conclusion, the proposed architecture, which separates mission logic (FSM in ROS2) from flight control (PX4), provides a robust and functional approach for autonomous UAV applications requiring complex mission interactions.